Examining state health and habitability laws and their relationship to state characteristics in the USA. Issue 4 (2nd October 2018) - Horwitz-Willis, Nate; Phillips, Martha; Ryan, Kevin; Bursac, Zoran; Ferguson, Alesia
Abstract : A variety of health conditions such as asthma, elevated blood lead levels (BLLs) in children, pesticide poisonings, and falls and trips injuries have been associated with substandard housing conditions, implying that improvement in housing can lead to improved health. This group of researchers previously developed and reported on a Habitability Element Rating Scores (HERS) to compare and rank the strength of habitability laws of US states. HERS considers a State's adoption of elements of Uniform Landlord and Tenant Act (URLTA) for upkeep of property (i.e., raw scores), and the potential of elements to influence tenant health (i.e., weighted scores). Here we examine the relationship of HERS raw scores with various state political and demographic features to investigate potential driving forces for the development/existence of comprehensive and equitable housing standards. Statistically significant associations reveal states tend to emphasise low or high HERS raw scores depending on factors such as rurality and the proportion of a state's legislative body, which indicates its political party affiliation. The group of states with moderately strong laws ( n = 11) also tended to be Southern states, with concomitantly higher proportions of minorities in the state, female renters heading the household, and renters living in poverty.